2021
DOI: 10.1111/tri.13927
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic oxygenated machine perfusion of the human pancreas for clinical islet isolation: a prospective feasibility study

Abstract: Summary Due to an increasing scarcity of pancreases with optimal donor characteristics, islet isolation centers utilize pancreases from extended criteria donors, such as from donation after circulatory death (DCD) donors, which are particularly susceptible to prolonged cold ischemia time (CIT). We hypothesized that hypothermic machine perfusion (HMP) can safely increase CIT. Five human DCD pancreases were subjected to 6 h of oxygenated HMP. Perfusion parameters, apoptosis, and edema were measured prior to isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In this study, we report our first experience of establishing HMPO 2 of the pancreas followed by a read‐out model of NR simulating the reperfusion period in transplantation. Similar to our work, Leemkuil et al in their recently published (2021) study [40] investigated the impact of HMPO 2 in human non‐transplanted DCD pancreases, compared with DBD SCS preserved pancreases, and used islet isolation to assess effect, evaluating the quality of the intervention in vitro and in vivo in an immunodeficient diabetic mouse model. They achieved successful islet isolation post‐HMPO 2 and observed no induction of oedema or apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, we report our first experience of establishing HMPO 2 of the pancreas followed by a read‐out model of NR simulating the reperfusion period in transplantation. Similar to our work, Leemkuil et al in their recently published (2021) study [40] investigated the impact of HMPO 2 in human non‐transplanted DCD pancreases, compared with DBD SCS preserved pancreases, and used islet isolation to assess effect, evaluating the quality of the intervention in vitro and in vivo in an immunodeficient diabetic mouse model. They achieved successful islet isolation post‐HMPO 2 and observed no induction of oedema or apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…Once the oxygen has converted mitochondrial metabolisms and rebuilt energy in the entire gland, the perfusion pressure could potentially be reduced in cases, where longer perfusion is needed to bridge logistical challenges and to avoid relevant edema and necrosis. Such findings were further paralleled by a greater islet viability isolated from discarded human pancreas after HOPE as shown by Doppenberg et al in 2021 [74]. More studies are required to identify such timings and to explore the acceptable SCS-duration before and after HOPE-treatment.…”
Section: Discussionmentioning
confidence: 83%
“…This literature review and cases series of HOPE in pancreas confirms what is reported with other organs. HMP should be performed at limited systolic pressures of £ 25mmHg for at least 2hrs, but ideally not more than 6-12hrs [5,7,74]. Once the oxygen has converted mitochondrial metabolisms and rebuilt energy in the entire gland, the perfusion pressure could potentially be reduced in cases, where longer perfusion is needed to bridge logistical challenges and to avoid relevant edema and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to prevent the organ fragment from barotrauma caused by the hypothermic conditions and reduce the risk of edema, HMP and HMP O 2 preservation was performed at 25 mm Hg in line with others. 19 In addition, by the use of a split model, we had to take in account the heterogeneity of the endocrine component of the pancreas, particularly in the selection of outcomes. [36][37][38][39] Our study underscores a significant variability in outcomes regarding IEQ/g between head and tail isolation from both DCD and DBD organs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current literature, [19][20][21][22][23][24] a systolic hypothermic pressure of 25 mm Hg was applied, delivered via the splenic artery with venous return via the splenic vein.…”
Section: Study Design and Perfusion Protocolmentioning
confidence: 99%